Casa da mulher brasileira: uma política pública para mulheres em situação de violência - Ayres, Cleison Ribeiro (2017)
The study under discussion refers to the implementation process of the Casa da Mulher Brasileira, in the City of Curitiba, which is a new public policy for welcoming and assisting women victims of violence, with a humanized and integral assistance, helping the access to specialized services and ensuring conditions for standing up to violence, empowerment and economic autonomy. In order to subsidize the discussion of the construction of public policies to face violence against women, it discusses concepts of gender, violence, violence against women, human rights, public policies and public policies for women. It also shows alarming data on the phenomenon of violence against women in Brazil, where 1 in 3 women have already suffered physical or sexual violence. The country also ranks fifth in relation to the number of women homicides in a list of 83 countries in relation to the number of homicides of women. The field research executed with five professionals, women, who worked on the implementation of the Casa da Mulher Brasileira in Curitiba, through qualitative interviews, aiming to present as a result a contextualization of this process. The Casa da Mulher Brasileira is an action defined in Article 3 of the Women Program: Living without Violence. Decree 8.086 established the Program on August 30, 2013, with the goal of integrating and expanding existing public services aimed at women in situations of violence, through the articulation of specialized services in the health, justice, social assistance and the promotion of financial autonomy. When it comes to reality, it responds to the provisions of the Maria da Penha Law, which establishes that the public policy to curb domestic and family violence against women be carried out by a set of actions articulated between the Union, the States, the Federal District and the Counties.